Student Learning Motivation in Control and Experiment Classes Using Role Playing Model’s Based On Traditional Games - Cinta Salim, Clarrisa Vicky Fidela; Raharjo, Tri Joko; Utomo, Udi (Educational Management, 2021)
The purpose of this study was to find differences in the learning motivation of students who learn to use a role playing model based on traditional games with conventional learning. The research was conducted using a quantitative research approach, namely a quasi-experimental method with a research design using a pretest-posttest control group design. This design involved two groups of subjects, one was given experimental treatment (experimental group) and the other was not given treatment (control class). The results showed that the students' learning motivation in the experimental class with the role playing model based on the traditional crank game was better than the control class with conventional learning. These results can be proven by the mean value of the experimental class motivation of 84.87, while the average result of the control class motivation is 68.37. It can be concluded that the use of role playing models based on traditional crank games has a better effect than conventional learning in increasing learning motivation of fourth grade elementary school students.